Transformation Toward Slow Fashion: A Literature Synthesis on the Ecological and Social Impacts of Fast Fashion - Sormin, Yoel Santo Andrianus; Albar, Yoga Matin (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2025)
This study synthesizes recent literature on the ecological and social impacts of fast fashion and explores slow fashion as a sustainable alternative. A Systematic Literature Review (SLR) was conducted following the PRISMA protocol, analyzing peer-reviewed articles published between 2014 and 2024 and indexed in Scopus, ScienceDirect, and Google Scholar. The findings indicate that fast fashion contributes approximately 10% of global carbon emissions, generates substantial volumes of textile and microplastic waste, and consumes excessive amounts of water. From a social perspective, the industry is strongly associated with labor exploitation, wage inequality, unsafe working conditions, and violations of workers’ rights, disproportionately affecting women in developing countries. As a response to these challenges, slow fashion emphasizes ethical production, conscious consumption, and product durability, with adoption influenced by consumers’ moral awareness and self-identity. This study contributes to sustainable fashion scholarship by integrating previously fragmented ecological and social evidence into a unified synthesis, identifying key research gaps, and proposing a conceptual framework to support the transition toward slow fashion. These contributions enhance academic understanding of the interconnected environmental and social consequences of fast fashion while offering strategic insights for researchers, practitioners, and policymakers seeking to advance sustainability within the global fashion industry.